Análisis de la efectividad de la cirugía laparoscópica totalmente extraperitoneal en hernias inguinales - Villanueva Polo, Carlos Alberto (2017)
Introduction: Hernioplasty is one of the most common operations in general surgery, laparoscopic surgery as treatment, has allowed to offer new expectations; The two most common laparoscopic techniques are TAPP and TEP (preperitoneal and totally extraperitoneal trans abdominal respectively). Objective: To analyze the effectiveness of laparoscopic PTO surgery in inguinal hernias. Materials and Methods: Observational, Prospective, Transverse, Descriptive Study. The necessary data were collected from the target population from October 15, 2014 to August 30, 2015, to later analyze the effectiveness of laparoscopic TEP surgery. Results: Regarding the evaluation of the postoperative pain scale, at the 4 weeks, 27.5% of patients presented VAS (visual analog scale) 2, 67.4% VAS 4, 22.5% VAS 6, 7.5% VAS 8, But none had VAS 10; In the recurrence of inguinal hernias, 5% of patients presented recurrences and 95% did not; And in complications 5% presented infection of the operative site and 95% had no complications